2018
DOI: 10.7196/ajhpe.2018.v10i2.980
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapy students’ use of social media for professional practice

Abstract: Background. The use of social media for professional practice is an emerging trend for healthcare professionals; however, limited literature exists on the phenomenon. Social media usage is prevalent among students, as it is incorporated into many health professions education curricula. This poses potential ethical dilemmas. Objective. To examine the nature of social media usage and knowledge of ethical considerations by occupational therapy (OT) students for professional purposes. Methods. A quantitative, cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The CSOTs sought methods to adapt to the NICU demands, including research using internet and textbook resources and contacting supervisors or mentors. Internet resources are commonly used to enhance professional development, especially in our technological advancing world 39,40,41,42 . They are beneficial to professionals needing to access information rapidly and cost-effectively, especially in rural areas 40 .…”
Section: Press For Masterymentioning
confidence: 99%
“…The CSOTs sought methods to adapt to the NICU demands, including research using internet and textbook resources and contacting supervisors or mentors. Internet resources are commonly used to enhance professional development, especially in our technological advancing world 39,40,41,42 . They are beneficial to professionals needing to access information rapidly and cost-effectively, especially in rural areas 40 .…”
Section: Press For Masterymentioning
confidence: 99%
“…Thus, a need has been established for tailored, platform-specific research. These calls for more concrete and tangible guidance have also been echoed in the research on students' perspectives [14,15]. Aligned with the calls described above, this study explores the following research question: 'How do occupational therapists use virtual communities ('groups') on Facebook for professional learning?…”
Section: Introductionmentioning
confidence: 89%
“…Most published empirical research on social media and learning in occupational therapy involves preregistration students [12][13][14][15]. Only two articles have focussed particularly on qualified practitioners [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…The use of social media in learning is addressed in another pair of articles. Naidoo et al [5] found that most students in their occupational therapy sample used some form of social media and that participants were aware of the ethical dilemmas inherent in using these media. Osaigbovo and Iwegim [6] report on the use of Instagram and Facebook to complement lectures in the teaching of medical microbiology in Nigeria.…”
Section: Editorialmentioning
confidence: 99%